The Influence of Active Learning By Integrating Religious Moderation Values On PPKN Learning Outcomes By Students - Sukri Badaruddin; Mirwan Fikri Muhkam; Nur Syajida; Nurmaida Nurmaida (Universitas of Muhammadiyah Makassar, 2024)
Active learning by integrating the values of religious moderation is one of the efforts to improve learning outcomes and instill the values of religious moderation among students. This study aims to determine the influence of active learning by integrating the values of religious moderation on learning outcomes in the Pancasila and Civic Education (PPKn) course by students. This study used a quantitative approach with expos facto research design. The study population was the first semester students of the Tarbiyah and Teacher Training Department at STAIN Majene which amounted to 205 students, while the sample number was 20 students. The sampling technique is random sampling technique. Research data were collected through learning outcomes tests and questionnaires. Data analysis using t-test. The results of the study with analysis on statistical tests significant ttests obtained the value of tcount = 4.34 and ttable = 1.34 at the significant level of α = 0.05, so that it can be concluded that tcount ttable then H0 is rejected and Ha is accepted this shows that there is a significant influence between active learning by integrating the values of religious moderation in PPKn courses into student learning outcomes. Students who participate in active learning with the integration of religious moderation values have better learning outcomes than students who participate in learning without active learning with the integration of religious moderation values.